Sexuality, Gender, and Culture: Latinas/Chicanas and their Sex Lives - González-López, Gloria (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This sixth volume of Syllabi and Instructional Materials for Chicano/a and Latino/a Studies in Sociology brings together some of the most recent pedagogical materials from academics teaching courses on Chicanos/as and Latinos/as through a sociological and interdisciplinary perspective. It includes topics on the historical and contemporary development of Chicano/a and Latino/a communities as tied to the economic, political and social factors influencing social inequality, the distinct historical experiences and cultural backgrounds of Latinos/as, the particularities and intersectionalities of race, class, gender, and sexuality in identity formation and in the structuring of institutions, and the national and international influences on race and ethnic relationships. Representing a range of courses offered in colleges and universities throughout the United States, this volume is organized along several of the critical teaching areas within Latino/a Sociology: Undergraduate and Graduate Survey Courses; Latino/a Communities and Identities; Gender, Sexuality, and Gender/Feminist Studies; Transnationalism and (Im)migration; Institutions; and Social Justice and Political Activism